Studi Literatur: Quantum Learning Sebagai Upaya Meningkatkan Hasil Belajar Siswa - Rachman Hakim; Neviyarni; Herman Nirwana (Citra Dharma Cindekia, 2022)
In an effort to improve student learning outcomes, the purpose of this research is to determine the increase in learning outcomes caused by the quantum learning learning model. In this study, the